Hubungan Antara Pengetahuan Dan Sikap Terhadap Gambar Penyakit Akibat Merokok Yang Terdapat Dalam Kemasan Rokok Dengan Perilaku Merokok Masyarakat Di Kelurahan Purwosari - Choiri, Choiri, Yuli Kusumawati, SKM., M. Kes (Epid), Anisa Catur Wijayanti, SKM., M.Epid (2015)
Choiri J410110041 Relationship Between Knowledge and Attitude of Diseases Due to Figures Contained on Smoking Cigarette Pack With Smoking Behavior in the Village Community Purwosari ABSTRAK Various ways have been done by the government in controlling tobacco products. Warning the dangers of smoking in the form of images of diseases caused by smoking on cigarette packs has been applied in Indonesia, but in kenyatanya number of smokers is still high. Data show in the village health center Purwosari Purwosari 914 households are still exposed to secondhand smoke. The purpose of this study was to analyze the relationship between knowledge and attitudes of respondents to the images of diseases caused by smoking on cigarette packs with smoking behavior. This type of research is an observational study with cross sectional design. The population was 914 households are still exposed to secondhand smoke. Of the sample calculations obtained 100 respondents selected by cluster random sampling technique. The data analysis used was chi square test. The results showed that there was no correlation between knowledge of the diseases caused by smoking images contained in cigarette packs with smoking behavior (p = 0.614) and there was a relationship between attitudes towards images of diseases caused by smoking and smoking behavior of the people in the village Purwosari (p = 0.001). Keywords : Knowledge, Attitude, Image Disease In Cigarette Packaging, Smoking Behavior